SUCCESSFUL MANAGEMENT OF A VIOLENT ASIAN ELEPHANT IN MUSTH UNDER XYLAZINE ANAESTHESIA - AHMED, J; AHMED, N; KYARONG, S (The Indian Journal of Animal Reproduction, 2022)
Successful management of a violent male Asian elephant (Elephas maximus) in musth was carried out using 700 mg Xylazine HCl to obtain desired standing anaesthesia. The legs of elephant were tied with chains and tethered by using special jute rope to prevent his movement until the musth period was over. In brief, better awareness of people on physiological behavoiur of elephants for detection of musth as well as to adopt appropriate management procedures is referred.